Inproved Math Connection Skills Through Online Learning Using MATH-UNWIR - Diki Mulyana; Mochammad Taufan; Luthfiyati Nurafifah (Universitas Muhammadiyah Mataram, 2021)
Advances in technology and learning carried out online due to the Covid-19 pandemic are the background for this research. Research objectives to determine the effectiveness of online learning using MATH-UNWIR in improving mathematical connection ability and online learning amid the pandemic Covid-19. This study uses quantitative research with a quasi-type experimental design, as well as a research design using pretest and posttest experimental classes. There are 15 students as research sample. The instruments used was connection skill test and questionare. The data obtained anylized with quantitative method. The average yield pretest was 56,33 and the posttest mean was 81,67. The results of the pretest posttest paired sample t-test showed that there was an average difference significant between pretest and posttest results, so that it brought to an effect of online learning using MATH-UNWIR on students' mathematical connections. The result of the N-Gain score was 0.57. That means it is in the medium category and shows a percentage of 57%. In this study it can be concluded that there is significant influence online learning’ using MATH-UNWIR to improve students' mathematical connections with the interpretation of the effectiveness of increasing mathematical connections quite effectively.Advances in technology and learning carried out online due to the Covid-19 pandemic are the background for this research. Research objectives to determine the effectiveness of online learning using MATH-UNWIR in improving mathematical connection ability and online learning amid the pandemic Covid-19. This study uses quantitative research with a quasi-type experimental design[L1] , as well as a research design using pretest and posttest experimental classes. There are 15 students as research sample. The instruments used was connection skill test and questionare. The data obtained anylized with quantitative method.The average yield pretest was 56,33 and the posttest mean was 81,67. The results of the pretestposttest paired sample t-test showed that there was an average difference significant between pretest and posttest results, so that it brought to an effect of online learning using MATH-UNWIR on students' mathematical connections. The result of the N-Gain score was 0.57. That means it is in the medium category and shows a percentage of 57%. In this study it can be concluded that there is significant influence online learning’ using MATH-UNWIR to improve students' mathematical connections with the interpretation of the effectiveness of increasing mathematical connections quite effectively. [L1]1. How many research subjects were involved (research sample)2. What research instruments do you use?3. How do you analyze the data you use?